Role of Judges in Handling Criminal Procedures for Children through Diversion of Justice - Agra Sulchantifa Ulul Amri; Akhmad Khisni (Law Development Journal, 2021)
This study aims to answer the problem: What is the role of the judge in handling cases of juvenile crime through fair diversion? How can the handling of criminal acts through fair diversion have an impact in the future? The research method used is sociological juridical. This research yields the result that judges play a role in handling criminal cases through diversion because the parties can be brought together by the judge for settlement by deliberation, consensus without going through a judicial process, so that through the path of peace. Because diversion upholds the values of Pancasila, especially the 2nd and 5th principles, humanity, social justice and dignified justice can be realized, namely humanizing humans, the protection of children from stigma, labeling, mental and moral reform can be overcome. In addition, it is very necessary to carry out guidance and strict supervision of children in their daily interactions so that the child does not commit another criminal act.